Alpine skiing: Effects of mental training program of junior representatives of the Czech republic - Hana Hřebíčková; Hana Válková; Sigmund Martin (Palacký University Olomouc, 2014)
BACKGROUND: Qualitative evaluation case study deals with the implementation of mental skills training program conducted with the Czech national junior alpine skiing team over a period of an annual training cycle and evaluation of its eﬀects by one of the members of the team. The concept of the study is based on current findings of sport psychology in the field of mental training in alpine skiing and other sports. The theoretical framework of the study is the socio-cognitive psychological paradigm (Bandura, 1986, 1997) and cognitive-behavioral approach. OBJECTIVE: The aim of the work is a qualitative evaluation of a program involving relaxation, concentration and imaginative techniques and goal setting by one of its participants. METHODS: Evaluation is carried out through semi-structured interview with the participant. The interview was analyzed in a scientific software Atlas.ti 6.2. The method of creating clusters were used for analysis. RESULTS: From the participants answers we understand the subjectively perceived benefit of the program based on understanding of the possibility of influencing the mental part of his performance. The racer presents that he learned the practical application of certain techniques of the mental preparation, particularly imagery and the mental plan of the race, which contributed to better coping with the race situation. The racer achieved the improvement in his FIS ranking standings in all the disciplines over the monitored season. Research findings are used in the proposal of practical recommendations for mental preparation in the training of top and performing skiers. CONCLUSION: An important factor in the success of the mental skills training program is cooperation of all interested participants, that are athlete, coach and psychologist. With applying the psychological techniques the key factors are mental support, encouragement, and development of confidence of the athlete in his own abilities. A well-designed training preparation and realistic expectations of an athlete and a coach should be commonplace. Mental training should not be limited to intervention only for one season, but cooperation of the team with some psychologist should be continuous.